Intercellular crosstalk between cancer cells and cancer-associated fibroblasts via extracellular vesicles - Yutaka Naito; Yusuke Yoshioka; Takahiro Ochiya (Cancer Cell International, 2022)
Abstract Intercellular communication plays an important role in cancer initiation and progression through direct contact and indirect interactions, such as via secretory molecules. Cancer-associated fibroblasts (CAFs) are one of the principal components of such communication with cancer cells, modulating cancer metastasis and tumour mechanics and influencing angiogenesis, the immune system, and therapeutic resistance. Over the past few years, there has been a significant increase in research on extracellular vesicles (EVs) as regulatory agents in intercellular communication. EVs enable the transfer of functional molecules, including proteins, mRNAs and microRNAs (miRNAs), to recipient cells. Cancer cells utilize EVs to dictate the specific characteristics of CAFs within the tumour microenvironment, thereby promoting cancer progression. In response to such “education” by cancer cells, CAFs contribute to cancer progression via EVs. In this review, we summarize experimental data indicating the pivotal roles of EVs in intercellular communication between cancer cells and CAFs.